A case of primary histiocytic sarcoma of the central nervous system - Rena Uno; Maki Kanzawa; Kazuhiro Tanaka; Takashi Sasayama; Yoshinori Kodama; Takanori Hirose; Tomoo Itoh (Elsevier, 2022)
Histiocytic sarcoma (HS) is a highly malignant hematopoietic neoplasm that rarely arises in the central nervous system (CNS). Only 36 cases of primary HS of the CNS (PHSCNS) have been reported in the literature. PHSCNS is also an aggressive tumor with a 7-month median survival time. To date, optimal treatment for PHSCNS has not been established yet. In this report, we present a case of PHSCNS developing in the cerebrum of a 44-year-old female. The tumor temporarily responded favorably to chemoradiotherapy despite multiple cerebral lesions and spinal dissemination. The patient, however, died 23 months after presentation. Histologically, large pleomorphic tumor cells were found intermingled with a variety of inflammatory cells including lymphoid cells, plasma cells, macrophages, eosinophils, and neutrophils. The tumor cells were immunohistochemically positive for CD163, CD68, p53, and p16. Although PHSCNS is extremely rare, it should be included in the differential diagnosis of pleomorphic CNS tumors, and a correct diagnosis may contribute to longer survival with intensive chemoradiotherapy.